A conceptual model for creating a favorable environment to reduce the production time and cost of production by e_collaboration - Mohammadjafari, Marjan; Ahmed, Shamsuddin; Md Dawal, Siti Zawiah; Zayandehroodi, Hadi (American-Eurasian Network for Scientific Information, Jordan, 2011)
The companies need to the implementation the projects on time within budget for achievement the success and competitive in the market. The prior researcher illustrated many method and model for development time in new product. For this purpose, in this research the author created a new model and allegation the electronic collaboration (Ecollaboration) by a project manager can create a favorable environment to reduce the production time and cost of production of new product. This model is composed of four construct: design, planning, procurement and production. For initially evaluated the model the author has done interview with 20 project managers in electronic industry in Iran. Analysis of the questions of the interview confirms the use of Ecollaboration by project management to successful projects in terms of time and cost.